GAYA KEPEMIMPINAN KEPALA SATUAN KERJA DALAM MENINGKATKAN EFEKTIVITAS KINERJA TENAGA KERJA - Feralda, Aulia A`yunina; Aryati, Ana Sofia (Jurnal Kewirausahaan dan Inovasi, 2023)
The Housing-Provision Work Unit is an organization established by the Ministry of Public Works and Housing. The organization works at the municipal level under the Directorate General of Housing. This research examines the performance gap between field workers in Gianyar and filed workers in Klungkung. The workers are field facilitators in technical and empowerment department. The objective of this research is to describe the style used by the work unit leaders from both regencies to enhance the effectiveness of the workers’ performance. The primary data of this qualitative descriptive research was harvested from observations and interviews with seven informants; they are field facilitators, assistant to field facilitators, and municipal coordinators, while the secondary data was acquired from relevant documents that help the accomplishment of this study. This research finds that the work unit leaders use participative leadership style. However, in order to improve performance effectiveness, they should apply two leadership styles that suit the real working situation and condition. Here participative and delegative styles need to be applied due to the complexity and the dynamics of the actual work.